Deposit of open scholarly publications: examining researcher engagement with UCT’s open access policy - Jackson, Seta (Library and Information Studies Centre (LISC), 2019)
The purpose of this study was to determine the reasons for the low deposit levels of peerreviewed, openly-licensed journal articles into the institutional repository, OpenUCT, by researchers at the University of Cape Town (UCT). The deposit of such materials into OpenUCT, which is managed by UCT Libraries, is mandated by the UCT Open Access Policy, which was approved by the University Council in June 2014. The study operates within a post-positivist research paradigm, utilising a predominantly quantitative research approach accompanied by some elements of qualitative inquiry. A survey questionnaire was used as the primary data collection method and distributed to UCT staff on academic conditions of service. A total of 116 responses out of 1,116 were received. The results indicate that almost half of respondents were aware of the existence of the Open Access Policy and its mandate to deposit into the OpenUCT repository and have either done so or intend doing so. Reasons for deposit and non-deposit were investigated, as well as the presence of a relationship between those who resist depositing and one of the theoretical frameworks guiding the study, that of Passive Innovation Resistance (PIR), which may be described as the propensity of an individual to decide against adopting an innovation without having had any prior interaction with it. A mild negative correlation was discovered between UCT researchers motivated to deposit their work into the repository and their levels of PIR, suggesting an inverse relationship between the two – the more motivated the researcher is to deposit, the lower their PIR levels are likely to be. However, due to the absence of a statistically significant p-value, the correlations are weak at best, and further investigation is required. Most significant for the study, however, is the finding that PIR scores for nondepositing researchers are markedly higher than for depositing researchers, suggesting that higher levels of PIR influence the non-engagement of researchers with the repository. A much smaller secondary investigation, in the form of interviews with UCT Libraries staff responsible for managing the OpenUCT repository, was also conducted. Questions used for the interviews were designed to evaluate the development, maintenance, and advocacy of the repository within the UCT community against identified critical success factors for institutional repositories - the other component of the theoretical framework guiding the study. This qualitative component, together with the findings from the survey questionnaire, are used to present a holistic and comprehensive picture of UCT researcher engagement with institutional repositories in general and OpenUCT in particular, and how UCT Libraries has addressed issues and challenges arising from its mandate, especially given its limited resources. Based on the findings of both avenues of inquiry, recommendations are proposed regarding ways in which UCT Libraries may further encourage engagement in its management of the repository as a sustainable, useful, growing enterprise that successfully showcases the research activity of the University.